Analysis of the World Health Organization Quality of life instrument's psychometric properties among Malaysian university students - Chua Bee Seok; Walton Wider; Jasmine Adela Mutang; Shazia Iqbal Hashmi; Murnizam Haji Halik (Journal for Re Attach Therapy and Developmental Diversities, 2023)
Introduction: While the World Health Organization Quality of Life (WHOQOL-BREF) scale has proven reliable in a multitude of psychological investigations, a comprehensive psychometric analysis has not been performed within the Malaysian context, particularly among university students. Objectives: This research intended to appraise the psychometric characteristics of the WHOQOL-BREF in a university student demographic within Malaysia. Methods: Utilizing snowball sampling, data was amassed from a sample size of 586 university students, hailing from varied regions in Malaysia. Results: The application of confirmatory factor analysis unveiled that the initial WHOQOL-BREF measurement model fell short of certain proposed model fitness benchmarks. However, through covariance analysis and the removal of three items possessing high covariance issues, the modified measurement model showcased an enhanced fit. It preserved a total of 21 items and fulfilled all recommended fitness indicators. Despite indicating satisfactory reliability, the study's outcomes suggest possible issues regarding the scale's convergent and discriminant validity. Conclusions: Further psychometric scrutiny is necessary to verify the appropriateness of the WHOQOL-BREF for Malaysian university students. Suggestions for prospective research were also considered.